Developing mathematical exercise software for visually impaired students - Janu Arlinwibowo; Yunus Mustaqim; Agung Prihandono; Fida Maisa Hana; Achmad Ridwan; Ade Ima Afifa Himayati (Research and Social Study Institute, 2021)
This study aims to develop an Android-based math exercises application for the visually impaired. This research is development research carried out with research steps, namely: (1) preliminary research, (2) prototyping stage, and (3) assessment phase. The research was conducted between April 2020 and December 2020. The material chosen in the application developed was a plan taught in 8 grade. The research process involved six experts in assessing the product, namely three mathematics education experts to assess the validity of the aspects of mathematical content, two blind education experts to assess visually impaired content suitability and accessibility, and 1 IT expert to assess product performance. The product was tested on nine visually impaired. The quality of teaching materials is based on three basic aspects: feasibility, practicality, and effectiveness. The conclusions of this study are: (1) the product has good quality because it has been declared feasible by experts, practical, which can be seen from the enthusiastic response and student testimonials, and is effective because it can be used to learn and measure abilities, (2) the application is divided into three sections, preamble (contains the opening tune and instructions for use), practice questions, and results. Application development is based on two elements, namely accessibility and compatibility of the content with the cognition of the visually impaired, (3) the question page consists of questions (will be read when entering the page and can be repeated when the user taps the question section), under the question, there is a question number. There is a question; answer choices are arranged twice in two (the answer choices will be read out when pressed by the user). There is an answer lock button at the very bottom, and (4) the visually impaired want an application that has a simple operating system, provides challenges to the user and has two functions, namely measuring their abilities and facilitating their learning.